(3aQO GdeYGdi dHOA GdCeGdjs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdedJLC Edi MQe Gddg Ydi Hf SdWGf Hf eMeO GdbGQi hSejJg aQO GdeYGdi dHOA GdCeGdi s
(3BNQgG (B:s
(3ai MGd JVQYce Edi Gddg hGSJZaGQce efg hGdMeO ddg QH GdYGdejf JeJ s
(3GdfSNI HgG MhGTs
(3efXheIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
Keywords: (3GdJhMjO hGdedd hGdfMds